Transcranial magnetic stimulation : proceedings of the International Symposium on Transcranial Magnetic Stimulation : Göttingen : 30 September to 4 October, 1998 - Paulus, Walter (Elsevier, 1999)
Hardbound. Transcranial magnetic stimulation (TMS) was introduced in 1985 as a new method for non-invasive and painless stimulation of the cerebral cortex. The method is based on the principle that a time-varying magnetic field will induce an electrical field which in neural tissue leads to activation of inhibitory and excitatory neurons. Therefore, TMS is a way to \"bypass\" electrical stimulation through the intact skull. The book shows that TMS has proven useful for many clinical and research purposes. The method of repetitive transcranial magnetic stimulation (rTMS) attracted particular interest when several studies claimed that electroconvulsive therapy in depression can be replaced by the non-invasive method of rTMS. rTMS opens a possibility to modulate neuroplasticity in the motor system and elsewhere in the brain. With 39 contributions this supplement provides a broad and critical up-to-date overview on almost every aspect of TMS. It summari
Electroencephalography and clinical neurophysiology. Suppl. no. 51
Keywords: mozek; Brain; mozková kůra; Cerebral Cortex; neurologie